Hydrogeochemical precursors of strong earthquakes in Kamchatka: further analysis - Biagi, P. F.; Piccolo, R.; Ermini, A.; Fujinawa, Y.; Kingsley, S. P.; Khatkevich, Y. M.; Gordeev, E. I. (CCSD, 2001)
International audience For many years, ion and gas content data have been collected from the groundwater of three deep wells in the southern area of the Kamchatka peninsula, Russia. In the last ten years, five earthquakes with M > 6.5 have occurred within 250 km of the wells. In a previous study, we investigated the possibility that the hydrogeochemical time series contained precursors. The technique used was to assume that each signal with an amplitude of three times the standard deviation is an irregularity and we then defined anomalies as irregularities occurring simultaneously in the data for more than one parameter at each well. Using this method, we identified 11 anomalies with 8 of them being possible successes and 3 being failures as earthquake precursors. Precursors were obtained for all five earthquakes that we considered. In this paper, we allow for the cross-correlation found between the gas data sets and in some cases, between the ion data sets. No cross-correlation has been found between gas and ion content data. Any correlation undermines the idea that an anomaly might be identified from irregularities appearing simultaneously on different parameters at each site. To refine the technique, we re-examine the hydrogeochemical data and define as anomalies those irregularities occurring simultaneously only in the data of two or more uncorrelated parameters. We then restricted the analysis to the cases of just the gas content data and the ion content data. In the first case, we found 6 successes and 2 failures, and in the second case, we found only 3 successes. In the first case, the precursors appear only for three of the five earthquakes we considered, and in the second case, only for two, but these are the earthquakes nearest to the wells. Interestingly, it shows that when a strict set of rules for defining an anomaly is used, the method produces only successes and when less restrictive rules are used, earthquakes further from the well are implicated, but at the cost of false alarms being ...